ELIMINATING TALENT ACQUISITION CHALLENGES IN THE NEW PARADIGM: A PROPOSED MODEL OF TALENT ACQUISITION PROCESS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
In the wake of post-pandemic work dynamics,  there’s talent shortage worldwide, even after  huge unemployment caused by temporary  closing-down of businesses and disrupted  economic activities due to COVID-19. There’s  enormous cost involved in talent screening,  assessment, and hiring after rounds of interview  and selection tests, however when newly hired  candidate doesn’t turn-up after receiving  offer or undergoing onboarding process,  whole activity-endeavor is squandered. The  new age TA manager face multifold issues in  identification, hunt, and sourcing of talent  in the ever-dynamic working environment in  post-pandemic context. The market of skilled  candidates is becoming fiercely competitive  in tech-enabled and AI supportive work-era,  posing further question of, how and where  to detect right talent in right time and at the  right cost, who stays with organization at least  till the time he starts generating return on  investment for the organization. The biggest  challenge talent acquisition managers face today  is, candidates turning ghosts after selection  and receiving employment-offer. It is a loss in  terms of time, money, efforts, and work. TA  managers are in constant search of solution to  cope-with this issue. In this paper we have made  an attempt to unravel this burgeoning problem  by posing two research questions; What factors  determine joining decision post-selection in  an organization? And; What strategy should  TA manager use to make dynamic talent join  the organization when selected after rigorous  screening and selection process?
Keywords: Talent Acquisition (TA); Talent Search; Acquisition Cost; Talent Ghosting